HERMENEUTIC LOGIC OF HISTORY ABOUT THE OPPORTUNITIES OF SEMANTIC REALITY - Meliakova, Yuliia Vasilyevna; Zhdanenko, Svitlana Borisovn; Kovalenko, Inna Igorevna; Salazar Cayuleo, Héctor; Kovalenko, Anna Viktorivna (Revista Notas Históricas y Geográficas, 2021)
The hermeneutic logic of history, on the one part, resolves the essential gnosiological controversies, and on the other, it considers purely technical issues of history understanding. This research is based on the non-classical approach to the understanding of history from the perspective of hermeneutic logic. Since the scientific positivist interpretation methodology is regarded as irrelevant, a new original technology of the dynamic history interpretation is offered. It converts history into an open “space of free access”. The dynamic textual model of history reproduction, which is based on the metonymic comparison of citations, sources and semantic paradoxes, serves as a way of establishing a special trans-communicative historic content. Despite a special ontological status of history as non-existent reality, historic events and phenomena undergo the dynamics of change in the presentation, substantive, virtual ad semantic aspects of its existence.